2023
DOI: 10.3390/agriculture13010126
|View full text |Cite
|
Sign up to set email alerts
|

Meat Quality in Rabbit (Oryctolagus cuniculus) and Hare (Lepus europaeus Pallas)—A Nutritional and Technological Perspective

Abstract: This study aimed to nutritionally and technologically characterize the meat produced by rabbit (Oryctolagus cuniculus, Flemish Giant breed, 50 farmed individuals) and hare (Lepus europaeus Pallas, 50 hunted individuals). Muscles were sampled from several carcass regions: dorsal torso—Longissimus dorsi (LD), thigh—Semimembranosus (SM), and upper arm—Triceps brachii (TB). To better depict the meat’s nutritional quality, the proximate composition and fatty acid profile were assessed, and then gross energy content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 75 publications
0
6
2
Order By: Relevance
“…Their supply to the human body is provided through the daily food ration. The two types of PUFA incorporated in muscle tissues play a favourable role in preventing or reducing human diseases [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their supply to the human body is provided through the daily food ration. The two types of PUFA incorporated in muscle tissues play a favourable role in preventing or reducing human diseases [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the past century, considerable progress has been made in improving human welfare worldwide [ 1 ]. However, the shifting of livestock production from the past century that aimed to ensure large quantities of high-value proteins and lipids to feed the population [ 2 , 3 ] is not sufficient for the future when considering the accelerated growth of the world population and increased life expectancy that could lead to a future “food crisis” [ 4 ]. Additionally, the impact of climate change is already being felt, highlighting the need for solutions for the sustainability of food and agricultural systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the biological aspect, the aforementioned species (roe deer, fallow deer, wild boar, rabbits) represent valuable animals due to their favorable nutritional content such as fatty acids [ 52 , 53 , 54 ], proteins with high biological value, essential amino acids, micronutrients or other compounds (carnitine, conjugated linoleic acid—CLA) [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the high nutritional value provided by a rich protein content with high biological value and the beneficial composition of favorable amino acids and essential fatty acids were mentioned by several authors such as Blaska et al [ 72 ], Quaresma et al [ 73 ], Valencak et al [ 23 ], and Frunză et al [ 54 ]. Similarly, other studies found interesting associations between game meat and the concept of a healthy product due to the limited content of saturated fat [ 74 ].…”
Section: Resultsmentioning
confidence: 99%